Economic effects of sustainable energy technology progress under carbon reduction targets: An analysis based on a dynamic multi-regional CGE model - Gao, Zhiyuan; Zhao, Ying; Li, Lianqing; Hao, Yu (Applied energy, 2024)
Advancing sustainable energy technologies (SET) is crucial for achieving carbon neutrality and effectively addressing climate change. Unlike most studies that focus on individual sustainable energy policies, this research constructs a recursive computable general equilibrium (CGE) model with comprehensive sustainable energy modules to analyze the macroeconomic effects of multiple policies related to SET advancement. Covering 8 regions, 13 energy sectors, and 37 intermediate input sectors, the study evaluates the economic and ecological impacts of various SET advancement scenarios from a global economic perspective, aiming for consistent carbon reduction. The findings reveal that : (1) SET implementation reduces electricity costs for residents, optimizes industrial structure, decreases fossil fuel usage, enhances energy use structure, and lowers carbon taxes; (2) the collective impact of renewable energies surpasses that of individual sources, with newer renewables like wind and solar power outperforming traditional ones such as hydropower and nuclear power; and (3) advancements in alternative energy technology have had diverse effects on the global energy environment and economic development. Based on these conclusions, we recommend that: (1) prioritizing the development of solar and wind power in the short term; (2) optimizing SET advancement mechanisms to support progress, including enhancing the market-based price formation for sustainable energy generation and promoting technological innovation and cost reduction; (3) encouraging a synergistic transformation of renewable energy with coal, gas power, and other sources to maximize policy synergies. •A recursive CGE model is constructed, featuring detailed renewable energy modules.•Renewable energy technologies significantly reduce carbon emissions.•The impacts of various renewable energy sources show heterogeneity.•Sole reliance on renewable energy cannot achieve carbon neutrality.•Rural residents stand to benefit greatly from advances in renewable energy technology.